Andrographis overcomes 5-fluorouracil-associated chemoresistance through inhibition of DKK1 in colorectal cancer. (5th April 2021) - Zhao, Yinghui; Wang, Chuanxin; Goel, Ajay
Abstract: Colorectal cancer (CRC) ranks as the third leading cause of cancer-related deaths in the USA. 5-Fluorouracil (5FU)-based chemotherapeutic drug remains a mainstay of CRC treatment. Unfortunately, 50–60% of patients eventually develop resistance to 5FU, leading to poor survival outcomes. Our previous work revealed that andrographis enhanced 5FU-induced anti-cancer activity, but the underlying mechanistic understanding largely remains unclear. In this study, we first established 5FU-resistant (5FUR) CRC cells and observed that combined treatment with andrographis-5FU in 5FUR cells exhibited superior effect on cell viability, proliferation, and colony formation capacity compared with individual treatments ( P < 0.001). To identify key genes and pathways responsible for 5FU resistance, we analyzed genome-wide transcriptomic profiling data from CRC patients who either responded or did not respond to 5FU. Among a panel of differentially expressed genes, Dickkopf-1 (DKK1) overexpression was a critical event for 5FU resistance. Moreover, andrographis significantly downregulated 5FU-induced DKK1 overexpression, accompanied with enhanced anti-tumor effects by abrogating downstream Akt-phosphorylation. In line with in vitro findings, andrographis enhanced 5FU-induced anti-cancer activity in mice xenografts and patient-derived tumoroids ( P < 0.01). In conclusion, our data provide novel evidence for andrographis-mediated reversal of 5FU resistance, highlighting its potential role as an adjunct to conventional chemotherapy in CRC. Abstract : We systematically demonstrated that andrographis overcomes 5FU-associated chemoresistance in 5FU-resiatant CRC cells by attenuating DKK1-dependent Akt-phosphorylation using multiple in vitro and in vivo models, revealing that andrographis might serve as potential adjunct to conventional chemotherapeutic drugs in patients with CRC.